The Theoretical and Practical Dimensions of International Economic Competitiveness - Rubaj, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: To link scientific information on international competitiveness with its potential application in economic policy. Research Design & Methods: The article presents an analysis of theoretical and practical aspects of international competitiveness, a presentation of ways of measuring this phenomenon and description of factors determining it. It discusses and presents key information on selected international competitiveness rankings. Findings: The analysis of information contained in international competitiveness rankings can be of key importance for improving the efficiency of state structures. Implications / Recommendations: International economic competitiveness is among the most important issues in economics due to the key importance of foreign trade for a nation’s development and the living standards of its inhabitants. Contribution: The article justifies the conducting and analysing of international competitiveness rankings. The resulting practical guidelines can indicate the directions reforms should take and how to improve the quality of a nation’s decision-making processes.